Preparation method of high-thermal-conductivity graphene foam with uniform spherical pore structure
By introducing polymer microspheres into a graphene oxide solution to form a composite film and then heat-treating it, the problem of pore size control in graphene foam was solved, the out-of-plane thermal conductivity of graphene foam was improved, the preparation cost was reduced, and the process was simplified.
Patent Information
- Application Number
- CN202511218704.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-28
- Publication Date
- 2025-12-02
AI Technical Summary
Existing technologies make it difficult to prepare graphene foam with adjustable pore size using simple and effective methods, which limits the improvement of out-of-plane thermal conductivity of graphene-based thermal interface materials, and also results in high preparation costs and long preparation times.
Polymer microspheres were used as templates to uniformly disperse in a graphene oxide solution, and a composite film was formed by assembly equipment. The microspheres were then removed by heat treatment to reduce the graphene oxide, resulting in graphene foam with a uniform spherical pore structure.
This study achieved a uniform porous structure for graphene foam, improved out-of-plane thermal conductivity, reduced manufacturing costs, and simplified the process.
Smart Images

Figure CN121044577A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermal management materials, specifically relating to a method for preparing a high thermal conductivity graphene foam with a uniform spherical pore structure. Background Technology
[0002] With the development of mobile electronics, new energy vehicles, 5G base stations, and high-power devices, the power of electronic devices is increasing exponentially while miniaturization is becoming increasingly prominent. Heat dissipation has become a significant obstacle to the development of these devices. Thermal interface materials can fill the air gap between the electronic device and the heat sink, improving heat dissipation efficiency. Therefore, the design and optimization of thermal interface materials are crucial for solving the heat dissipation problem of high-power electronic devices.
[0003] Graphene is currently the material with the highest known thermal conductivity (5300 W / m·K), and graphene-based thermal interface materials exhibit high thermal conductivity and good heat dissipation. However, due to graphene's two-dimensional sheet structure, electron and phonon heat transfer exhibits anisotropy, resulting in low thermal conductivity in the vertical direction. Therefore, improving the out-of-plane thermal conductivity of graphene-based thermal interface materials has become a bottleneck for their application. Recently, CN 1055427298A disclosed a method for preparing vertically oriented graphene sheet / polymer thermal interface materials. By vertically oriented graphene sheets, the thermal conductivity in the vertical direction is improved, while PDMS is used to fill the pores, enhancing the material's strength and thermal conductivity. However, vertically oriented graphene sheets increase the compressive modulus, leading to increased contact thermal resistance between the upper and lower surfaces, hindering heat transfer. CN 114214042A discloses an application of graphene film as a high-temperature resistant thermal interface material or heat dissipation film material. Using a three-dimensionally interconnected, high-porosity, high-density porous metal as a template, a three-dimensionally interconnected porous graphene framework is obtained through chemical vapor deposition. The graphene film exhibits high crystallinity and flexibility, and excellent thermal conductivity in both in-plane and perpendicular directions. However, this process relies on a disposable porous metal template, resulting in high preparation costs, long preparation time, and difficulty in controlling the pore structure. Therefore, how to prepare graphene foam with adjustable pores through a simple and effective method is an urgent problem to be solved. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a method for template-assisted preparation of highly thermally conductive graphene foam with a uniform spherical porous structure. This method involves uniformly dispersing polymer microspheres as templates in a graphene oxide solution. Then, using an assembly device, the microspheres and graphene oxide are tightly bonded through hydrogen bonds to obtain a composite film. Finally, the microspheres are removed and the graphene oxide is reduced through two heat treatments, resulting in a graphene foam with a uniform spherical porous structure. The introduction of polymer microspheres enables the graphene foam to form a uniform porous structure, inducing some graphene sheets to align vertically, thereby forming a continuous, highly thermally conductive network. Simultaneously, it promotes defect repair and grain growth during graphitization, ultimately yielding a highly thermally conductive graphene foam with a uniform spherical porous structure.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows:
[0006] This invention provides a method for preparing a high thermal conductivity graphene foam with a uniform spherical pore structure, comprising the following steps:
[0007] (1) The graphene oxide solution was ultrasonically dispersed and then uniformly mixed with a polymer microsphere emulsion, and a composite film was prepared by ordered assembly.
[0008] (2) The composite film is heat-treated to remove the microspheres and obtain reduced graphene oxide foam.
[0009] (3) The reduced graphene oxide foam is graphitized to obtain high thermal conductivity graphene foam.
[0010] In one alternative embodiment, the graphene oxide sheet diameter in step (1) is 1-50 μm.
[0011] In one optional embodiment, the polymer microspheres in step (1) are one or more of polymethyl methacrylate (PMMA), polystyrene (PS), polyimide (PI), and polyhydroxy fatty acid (PHA); the particle size of the polymer microspheres is 1-10 μm.
[0012] In one optional embodiment, the concentration of the polymer microsphere emulsion in step (1) is 100-200 mg / ml, and the volume ratio of the graphene oxide solution to the polymer microsphere emulsion is 30-600.
[0013] In one optional embodiment, the equipment assembled in step (1) is a vacuum filter bottle or a coating machine, the vacuum filtration time is 24-72 h, the stepping speed of the coating machine is 3-5 m / min, and the scraper height is 3-6 mm.
[0014] In one optional embodiment, the heat treatment conditions in step (2) are as follows: the inert atmosphere is one of nitrogen, helium or argon, the heat treatment temperature is 800-1500 ℃, the heating rate is 1-10 ℃ / min, and the isothermal time is 30min-6 h.
[0015] In one optional embodiment, the graphitization conditions in step (3) are: the inert atmosphere is one of nitrogen, helium or argon, the graphitization temperature is 2800-3000 ℃, and the constant temperature time is 2-8 h.
[0016] In another aspect, the present invention provides graphene foam prepared by the preparation method described in the first aspect, wherein the apparent density of the graphene foam is 0.05-0.6 g / cm³. 3 Out-of-plane thermal diffusivity greater than 10 mm 2 / s, Lc is 50-80 nm.
[0017] In another aspect, the present invention provides a thermal interface material, including graphene foam prepared by the preparation method described in the first aspect.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0019] 1. This invention prepares a thin film by compositing graphene oxide with microspheres, and then removes the microspheres while reducing the graphene oxide through heat treatment to obtain graphene foam. The introduction of microspheres enables the graphene foam to form a uniform porous structure and construct a continuous thermally conductive carbon layer network, thereby effectively improving the longitudinal thermal conductivity of the graphene foam and thus exhibiting excellent out-of-plane thermal conductivity.
[0020] 2. The presence of microspheres hinders the loss of C atoms during carbonization and promotes the generation of sp3 hybrid C atoms, which is beneficial for defect repair and grain growth during graphitization, thereby significantly improving thermal conductivity.
[0021] 3. The preparation method of the present invention has the advantages of stable raw material source, batch stability, low cost, adjustable pore size, and simple processing technology, and is easy to realize the preparation of high thermal conductivity graphene-based thermal interface materials. Attached Figure Description
[0022] Figure 1 This is a SEM image of the graphene foam prepared in Example 1.
[0023] Figure 2 The image shows a SEM image of the graphene foam prepared in Comparative Example 1.
[0024] Figure 3 The graphene foam prepared in Examples 1-5 and Comparative Example 1 has thermal diffusion properties. Detailed Implementation
[0025] To facilitate understanding of the present invention, a more comprehensive description will be given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.
[0026] Example 1
[0027] (1) Take 50 ml of graphene oxide solution with a concentration of 12 mg / ml (the average diameter of graphene oxide sheets is about 5 μm) and add a certain amount of deionized water to dilute to 3 mg / ml. Stir with a magnetic stirrer for 20 min, and then put the solution into an ultrasonic cleaner to disperse for 30 min to obtain graphene oxide solution.
[0028] (2) Weigh 2 g of polymethyl methacrylate (PMMA) microsphere powder (microsphere particle size is about 5 μm), add 10 ml of ethanol, stir with a magnetic stirrer for 20 min, and then put the solution into an ultrasonic cleaner to disperse for 30 min to obtain PMMA microsphere emulsion.
[0029] (3) Add 0.075 ml of PMMA microsphere emulsion to 20 ml of dispersed graphene oxide solution, stir with a magnetic stirrer for 20 min, and then place the solution into an ultrasonic cleaner to disperse for 30 min to obtain a mixture of the two.
[0030] (4) Take 20 ml of the mixture from step (3), transfer it to a vacuum filtration flask, and vacuum filter for 24 h to obtain a composite filter cake; then transfer it to an oven and dry it at 45 ℃ for 8 h to obtain a composite film.
[0031] (5) The dried composite film is placed in a tube furnace and heated to 800 ℃ at a heating rate of 5 ℃ / min under an argon atmosphere. The temperature is held for 30 min and then cooled to room temperature to obtain reduced graphene oxide foam.
[0032] (6) The reduced graphene oxide foam was placed in a graphitization furnace at a graphitization temperature of 2800 ℃ and a holding time of 2 h to obtain graphitized graphene foam.
[0033] The graphene foam prepared in Example 1 had an interlayer spacing of 0.33759 nm, an Lc of 65.4 nm, and a density of 0.182 g / cm³. 3 Tests showed that the in-surface thermal diffusivity of this graphene foam reached 501 mm². 2 / s (5% improvement over Comparative Example 1), out-of-plane thermal diffusivity 30.2 mm 2 / s (221.3% improvement compared to Comparative Example 1).
[0034] Example 2
[0035] (1) Take 50 ml of graphene oxide solution with a concentration of 12 mg / ml (the average diameter of graphene oxide sheets is about 5 μm) and add a certain amount of deionized water to dilute to 3 mg / ml. Stir with a magnetic stirrer for 20 min, and then put the solution into an ultrasonic cleaner to disperse for 30 min to obtain graphene oxide solution.
[0036] (2) Weigh 2 g of PMMA microsphere powder (microsphere particle size is about 5 μm), add 10 ml of ethanol, stir with a magnetic stirrer for 20 min, and then put the solution into an ultrasonic cleaner to disperse for 30 min to obtain PMMA microsphere emulsion.
[0037] (3) Add 0.1 ml of PMMA microsphere emulsion to 20 ml of dispersed graphene oxide solution, stir with a magnetic stirrer for 20 min, and then place the solution into an ultrasonic cleaner to disperse for 30 min to obtain a mixture of the two.
[0038] (4) Take 20 ml of the mixture from step (3), transfer it to a vacuum filtration flask, and vacuum filter for 24 h to obtain a composite filter cake; then transfer it to an oven and dry it at 45 ℃ for 8 h to obtain a composite film.
[0039] (5) The dried composite film is placed in a tube furnace and heated to 800 ℃ at a heating rate of 5 ℃ / min under an argon atmosphere. The temperature is held for 30 min and then cooled to room temperature to obtain reduced graphene oxide foam.
[0040] (6) The reduced graphene oxide foam was placed in a graphitization furnace at a graphitization temperature of 2800 ℃ and a holding time of 2 h to obtain graphitized graphene foam.
[0041] The graphene foam prepared in Example 2 had an interlayer spacing of 0.33736 nm, an Lc of 70.8 nm, and a density of 0.148 g / cm³. 3 Tests showed that the in-surface thermal diffusivity of this graphene foam reached 529 mm². 2 / s (a 10.9% improvement over Comparative Example 1), out-of-plane thermal diffusivity 31.4 mm 2 / s (234.8% improvement compared to Comparative Example 1).
[0042] Example 3
[0043] (1) Take 50 ml of graphene oxide solution with a concentration of 12 mg / ml (the average diameter of graphene oxide sheets is about 5 μm) and add a certain amount of deionized water to dilute to 3 mg / ml. Stir with a magnetic stirrer for 20 min, and then put the solution into an ultrasonic cleaner to disperse for 30 min to obtain graphene oxide solution.
[0044] (2) Weigh 2 g of PMMA microsphere powder (microsphere particle size is about 5 μm), add 10 ml of ethanol, stir with a magnetic stirrer for 20 min, and then put the solution into an ultrasonic cleaner to disperse for 30 min to obtain PMMA microsphere emulsion.
[0045] (3) Add 0.15 ml of PMMA microsphere emulsion to 20 ml of dispersed graphene oxide solution, stir with a magnetic stirrer for 20 min, and then place the solution into an ultrasonic cleaner for 30 min to obtain a mixture of the two.
[0046] (4) Take 20 ml of the mixture from step (3), transfer it to a vacuum filtration flask, and vacuum filter for 24 h to obtain a composite filter cake; then transfer it to an oven and dry it at 45 ℃ for 8 h to obtain a composite film.
[0047] (5) The dried composite film is placed in a tube furnace and heated to 800 ℃ at a heating rate of 5 ℃ / min under an argon atmosphere. The temperature is held for 30 min and then cooled to room temperature to obtain reduced graphene oxide foam.
[0048] (6) The reduced graphene oxide foam was placed in a graphitization furnace at a graphitization temperature of 2800 ℃ and a holding time of 2h to obtain graphitized graphene foam.
[0049] The graphene foam prepared in Example 3 had an interlayer spacing of 0.33721 nm, an Lc of 71.1 nm, and a density of 0.109 g / cm³. 3 Tests showed that the in-surface thermal diffusivity of this graphene foam reached 602 mm². 2 / s (a 26.2% improvement over Comparative Example 1), out-of-plane thermal diffusivity 51.6 mm 2 / s (448.9% improvement compared to Comparative Example 1).
[0050] Example 4
[0051] (1) Take 50 ml of graphene oxide solution with a concentration of 12 mg / ml (the average diameter of graphene oxide sheets is about 5 μm) and add a certain amount of deionized water to dilute to 3 mg / ml. Stir with a magnetic stirrer for 20 min, and then put the solution into an ultrasonic cleaner to disperse for 30 min to obtain graphene oxide solution.
[0052] (2) Weigh 2 g of polyimide (PI) microsphere powder (microsphere particle size is about 5 μm), add 10 ml of ethanol, stir with a magnetic stirrer for 20 min, and then put the solution into an ultrasonic cleaner to disperse for 30 min to obtain PI microsphere emulsion.
[0053] (3) Add 0.3 ml of PI microsphere emulsion to 20 ml of dispersed graphene oxide solution, stir with a magnetic stirrer for 20 min, and then place the solution into an ultrasonic cleaner to disperse for 30 min to obtain a mixture of the two.
[0054] (4) Take 20 ml of the mixture from step (3), transfer it to a vacuum filtration flask, and vacuum filter for 24 h to obtain a composite filter cake; then transfer it to an oven and dry it at 45 ℃ for 8 h to obtain a composite film.
[0055] (5) The dried composite film is placed in a tube furnace and heated to 800 ℃ at a heating rate of 5 ℃ / min under an argon atmosphere. The temperature is held for 30 min and then cooled to room temperature to obtain reduced graphene oxide foam.
[0056] (6) The reduced graphene oxide foam was placed in a graphitization furnace at a graphitization temperature of 2800 ℃ and a holding time of 2 h to obtain graphitized graphene foam.
[0057] The graphene foam prepared in Example 4 had an interlayer spacing of 0.33739 nm, an Lc of 67.9 nm, and a density of 0.087 g / cm³. 3 Tests showed that the in-surface thermal diffusivity of this graphene foam reached 522 mm². 2 / s (a 9.4% improvement over Comparative Example 1), out-of-plane thermal diffusivity 33.2 mm 2 / s (253.2% improvement compared to Comparative Example 1).
[0058] Example 5
[0059] (1) Take 50 ml of graphene oxide solution with a concentration of 12 mg / ml (the average diameter of graphene oxide sheets is about 5 μm) and add a certain amount of deionized water to dilute to 3 mg / ml. Stir with a magnetic stirrer for 20 min, and then put the solution into an ultrasonic cleaner to disperse for 30 min to obtain graphene oxide solution.
[0060] (2) Weigh 2 g of PI microsphere powder (microsphere particle size is about 5 μm), add 10 ml of ethanol, stir with a magnetic stirrer for 20 min, and then put the solution into an ultrasonic cleaner to disperse for 30 min to obtain PI microsphere emulsion.
[0061] (3) Add 0.6 ml of PI microsphere emulsion to 20 ml of dispersed graphene oxide solution, stir with a magnetic stirrer for 20 min, and then place the solution into an ultrasonic cleaner to disperse for 30 min to obtain a mixture of the two.
[0062] (4) Take 20 ml of the mixture from step (3), transfer it to a vacuum filtration flask, and vacuum filter for 24 h to obtain a composite filter cake; then transfer it to an oven and dry it at 45 ℃ for 8 h to obtain a composite film.
[0063] (5) The dried composite film is placed in a tube furnace and heated to 800 ℃ at a heating rate of 5 ℃ / min under an argon atmosphere. The temperature is held for 30 min and then cooled to room temperature to obtain reduced graphene oxide foam.
[0064] (6) The reduced graphene oxide foam was placed in a graphitization furnace at a graphitization temperature of 2800 ℃ and a holding time of 2 h to obtain graphitized graphene foam.
[0065] The graphene foam prepared in Example 5 had an interlayer spacing of 0.33907 nm, an Lc of 59.4 nm, and a density of 0.072 g / cm³. 3 Tests showed that the in-surface thermal diffusivity of this graphene foam reached 482 mm². 2 / s (1.0% improvement compared to Comparative Example 1), out-of-plane thermal diffusivity 30.5 mm 2 / s (224.5% improvement compared to Comparative Example 1).
[0066] Comparative Example 1
[0067] The difference between this comparative example and Example 1 is that PMMA or PI emulsion is not added in step (3) of Comparative Example 1. The other steps and parameters of Comparative Example 1 are the same as those of Example 1.
[0068] The graphene foam prepared in Comparative Example 1 had an interlayer spacing of 0.33681 nm, an Lc of 57.2 nm, and a density of 0.207 g / cm³. 3 Tests showed that the in-surface thermal diffusivity of this graphene foam reached 477 mm². 2 / s, out-of-plane thermal diffusivity 9.4 mm 2 / s.
[0069] The above description is only for better explaining the embodiments of the present invention and is not intended to limit them. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention shall fall within the scope of the present invention.
Claims
1. A method for preparing a high thermal conductivity graphene foam with a uniform spherical pore structure, characterized in that, Includes the following steps: (1) The graphene oxide solution was ultrasonically dispersed and then uniformly mixed with a polymer microsphere emulsion, and a composite film was prepared by ordered assembly. (2) The composite film is heat-treated to remove the microspheres and obtain reduced graphene oxide foam. (3) The reduced graphene oxide foam is graphitized to obtain high thermal conductivity graphene foam.
2. The preparation method according to claim 1, characterized in that, In step (1), the diameter of the graphene oxide sheets is 1-50 μm.
3. The preparation method according to claim 1, characterized in that, In step (1), the polymer microspheres are one or more of polymethyl methacrylate, polystyrene, polyimide, and polyhydroxy fatty acids; the particle size of the polymer microspheres is 1-10 μm.
4. The preparation method according to claim 1, characterized in that, In step (1), the concentration of the polymer microsphere emulsion is 100-200 mg / ml, and the volume ratio of the graphene oxide solution to the polymer microsphere emulsion is 30-600.
5. The preparation method according to claim 1, characterized in that, The equipment assembled in step (1) is a vacuum filter bottle or a coating machine. The vacuum filtration time is 24-72 h, the stepping speed of the coating machine is 3-5 m / min, and the scraper height is 3-6 mm.
6. The preparation method according to claim 1, characterized in that, The conditions for heat treatment in step (2) are as follows: the inert atmosphere is one of nitrogen, helium or argon, the heat treatment temperature is 800-1500 ℃, the heating rate is 1-10 ℃ / min, and the holding time is 30 min-6 h.
7. The preparation method according to claim 1, characterized in that, The graphitization conditions in step (3) are: the inert atmosphere is one of nitrogen, helium or argon, the graphitization temperature is 2800-3000 ℃, and the constant temperature time is 2-8 h.
8. The graphene foam prepared by the preparation method according to any one of claims 1-7, characterized in that, The apparent density of the graphene foam is 0.05-0.6 g / cm³. 3 Out-of-plane thermal diffusivity greater than 10 mm 2 / s, L c is 50-80 nm.
9. A thermal interface material, characterized in that, The graphene foam includes the preparation method described in any one of claims 1-7.
Citation Information
Patent Citations
Application of graphene film as high-temperature-resistant thermal interface material or heat dissipation film material
CN114214042A